Effect of Severity Factor on the Subcritical Water and Enzymatic Hydrolysis of Coconut Husk for Reducing Sugar Production - Maktum Muharja; Nur Fadhilah; Rizki Fitria Darmayanti; Hanny Frans Sangian; Tantular Nurtono; Arief Widjaja (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Preventing the further degradation of monomeric or oligomeric sugar into by-product during biomass conversion is one of the challenges for fermentable sugar production. In this study, the performance of subcritical water (SCW) and enzymatic hydrolysis of coconut husk toward reducing sugar production was investigated using a severity factor (SF) approach. Furthermore, the optimal condition of SCW was optimized using response surface methodology (RSM), where the composition changes of lignocellulose and sugar yield as responses. From the results, at low SF of SCW, sugar yield escalated as increasing SF value. In the enzymatic hydrolysis process, the effect of SCW pressure is a significant factor enhancing sugar yield. A maximum total sugar yield was attained on the mild SF condition of 2.86. From this work, it was known that the SF approach is sufficient parameter to evaluate the SCW and enzymatic hydrolysis of coconut husk. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).